2013
DOI: 10.1039/c3ob40368h
|View full text |Cite
|
Sign up to set email alerts
|

Novel 5-anilinoquinazoline-8-nitro derivatives as inhibitors of VEGFR-2 tyrosine kinase: synthesis, biological evaluation and molecular docking

Abstract: Vascular endothelial growth factor receptor-2 (VEGFR-2) kinase inhibition is a well-established strategy to promptly tackle tumor growth by suppression of angiogenesis. We report herein a series of 5-anilinoquinazoline derivatives substituted by 1,3-disubstituted urea. All the newly synthesized compounds described were evaluated for VEGFR-2 kinase inhibition and antiproliferative activity against various cancer cells. The novel 1-aryl, 3-aryl-disubstituted urea quinazolines were effective VEGFR-2 kinase inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…We have succeeded in using a structure‐based approach to discover a class of quinazoline derivatives that inhibit the VEGFR‐2 protein . In this study, we attempted to develop indole‐2‐carbohydrazide derivatives as anti‐angiogenesis agents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have succeeded in using a structure‐based approach to discover a class of quinazoline derivatives that inhibit the VEGFR‐2 protein . In this study, we attempted to develop indole‐2‐carbohydrazide derivatives as anti‐angiogenesis agents.…”
Section: Introductionmentioning
confidence: 99%
“…[33] We have succeeded in using as tructure-based approach to discover ac lass of quinazolined erivatives that inhibitt he VEGFR-2 protein. [34] In this study,w ea ttempted to develop indole-2-carbohydrazide derivativesa sa nti-angiogenesis agents. Initially,a fter three rounds of virtual screenings using Dock 6.0, [35,36] AutoDock 4.0, [37] andG oldDock 5.0, [38] eight of An ovel series of indole-2-carbohydrazide derivatives were synthesized, characterized, and evaluated for theira ntiproliferative activitiesa gainst two cancerc ell lines, HCT116 and SW480, and an ormal human fetal lung fibroblastc ell line, MRC-5.A mong this series, compound 24 f displayed potent cytotoxic activities in vitro against HCT116 and SW480c ell lines with GI 50 values of 8.1 and 7.9 mm,r espectively,a nd was inactive against MRC-5 cells.…”
Section: Introductionmentioning
confidence: 99%
“…[66] Then compounds 3 and aryl isonitrile ester 4 were held at reflux for 2-4 hours to obtain target compounds 5.A dditionally,t he synthesis of 2-arylbenzimidazole derivatives is showni n Scheme1b. [66] Then compounds 3 and aryl isonitrile ester 4 were held at reflux for 2-4 hours to obtain target compounds 5.A dditionally,t he synthesis of 2-arylbenzimidazole derivatives is showni n Scheme1b.…”
Section: Resultsmentioning
confidence: 99%
“…Recently,6-substituted benzoxazole or benzimidazole derivatives have been developed as multi-kinasei nhibitors, including tyrosine and serine/threonine kinases. [36] In the quest to find better anti-angiogenic agents, and as ac ontinuation of our previous studies on anticancer drug discovery, [66][67][68][69][70][71][72][73] we designed af amily of compoundsc ontaining 6-arylurea-2-arylbenzoxazoles and 6-arylurea-2-arylbenzimidazoles, with the goal of findingn ew potent anticancer agents ( Figure 2). [65] The X-ray crystallographic elucidation of the complex between 1 and VEGFR-2 demonstrated that the 2-fluoro-5-(trifluoromethyl)phenyl moiety is buried in the hydrophobic pocket, and the benzimidazole ring occupies the adenine pocket, interacting with the Cys919 residue, while the central arylurea linker is bent towardt he "hinge" region of the receptor.T herefore, we speculated that the length of the urea linker can be shortened appropriatelyt ob etter match the active site ( Figure 2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation